Geo - location by proxy : approaching VGI from the perspective of geographic context :Powerpoint - Verplanke, J.J. (University of Twente, 2020)
This lecture presents: VGI and a reuse example; Reuse of VGI; A concept to bind them; 3 Dimensions of VGI; Importance of context; Purpose.